NEW PERSPECTIVES ON ALZHEIMER’S DISEASE TREATMENT: A STRUCTURED SCIENTIFIC REVIEW (2020–2025) - Hanna Wilska; Antoni Liebert; Natalia Klimek; Adam Niedziela; Dominik Domoń; Martyna Kaplińska; Dominika Domanowska (International Journal of Innovative Technologies in Social Science, 2025)
Background: Alzheimer’s disease (AD) remains the leading cause of dementia worldwide, with current therapies offering only modest symptomatic benefits. In recent years, multiple mechanistic approaches have advanced into clinical testing, reshaping therapeutic strategies.Objective: This review synthesizes evidence from the past five years on emerging treatments for AD, highlighting novel disease-modifying agents, biomarker innovations, and adjunctive strategies.Methods: A structured literature search was conducted across PubMed, Embase, and ClinicalTrials.gov for studies published between January 2020 and July 2025. Peer-reviewed articles, pivotal clinical trials, and regulatory documents were included. Findings were organized into five thematic domains: anti-amyloid therapies, tau-targeted interventions, neuroinflammation and innate immunity, metabolic and repurposed drugs, and emerging technologies for drug delivery and diagnostics.Results: Anti-amyloid monoclonal antibodies, including lecanemab and donanemab, demonstrated clinically meaningful slowing of cognitive decline in early AD, leading to regulatory approvals. However, safety concerns, particularly amyloid-related imaging abnormalities, remain critical considerations. Tau-targeting therapies have shown modest biomarker and clinical effects, while immune-modulating agents, such as TREM2 agonists, represent promising novel approaches. GLP-1 receptor agonists, intranasal insulin, and lifestyle-based multidomain interventions target metabolic and systemic contributors to AD, with mixed but encouraging results. Technological advances, including focused ultrasound for blood–brain barrier opening and blood-based biomarkers (e.g., plasma p-tau217, GFAP, NfL), are transforming diagnosis and trial design. Despite progress, challenges remain regarding safety, generalizability, and equitable access.Conclusion: AD therapeutics are entering a transformative phase, shifting from purely symptomatic management toward disease modification. Anti-amyloid therapies provide proof of principle but require optimization of safety and implementation. Parallel efforts targeting tau, neuroinflammation, and systemic pathways, coupled with advances in biomarker-driven precision medicine, suggest that future management will likely rely on combination strategies tailored to individual biological profiles.